Design and implementation of log domain decoder - Mahmood Farhan Mosleh; Fadhil Sahib Hasan; Ruaa Majeed Azeez (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Low-Density-Parity-Check (LDPC) code has become famous in communications systems for error correction, as an advantage of the robust performance in correcting errors and the ability to meet all the requirements of the 5G system. However, the mot challenge faced researchers is the hardware implementation, because of higher complexity and long run-time. In this paper, an efficient and optimum design for log domain decoder has been implemented using Xilinx system generator with FPGA device Kintex 7 (XC7K325T-2FFG900C). Results confirm that the proposed decoder gives a Bit Error Rate (BER) very closed to theory calculations which illustrate that this decoder is suitable for next generation demand which needs high data rate with very low BER.